2013
DOI: 10.5152/akd.2013.102
|View full text |Cite
|
Sign up to set email alerts
|

The role of tenascin-C and oxidative stress in rheumatic and congenital heart valve diseases: an observational study

Abstract: Objective: The aim of this study was to evaluate the association of tenascin-C (TnC) and total oxidant-antioxidant status to rheumatic or congenital heart valve diseases (HVD) in pediatric patients. Methods: Fifty pediatric patients (25 rheumatic HVD patients and 25 congenital HVD patients) and 20 healthy age-matched control subjects, aged 3-17 years, were enrolled in this observational and cross-sectional study. Serum total antioxidant capacity (TAC), total oxidant status (TOS), oxidative stress index (OSI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
0
11
1
2
Order By: Relevance
“…An increasing number of studies have examined the clinical utility of serum TNC levels in patients with various heart diseases (reviewed in [ 149 , 174 , 175 ]), such as non-compaction/hypertrabeculation [ 176 ], hypertrophic cardiomyopathy [ 177 ], heart failure with ischemic heart disease, Kawasaki disease [ 178 ], rheumatic heart disease, and congenital heart disease in pediatric patients [ 179 , 180 ].…”
Section: Clinical Application Of Tncmentioning
confidence: 99%
“…An increasing number of studies have examined the clinical utility of serum TNC levels in patients with various heart diseases (reviewed in [ 149 , 174 , 175 ]), such as non-compaction/hypertrabeculation [ 176 ], hypertrophic cardiomyopathy [ 177 ], heart failure with ischemic heart disease, Kawasaki disease [ 178 ], rheumatic heart disease, and congenital heart disease in pediatric patients [ 179 , 180 ].…”
Section: Clinical Application Of Tncmentioning
confidence: 99%
“…Further, complement activation may induce some inflammatory effects, such as the expression of adhesion molecules, chemotaxis and leukocytes activation, the release of ROS, as well as the secretion of cytokines and chemokines [25]. There are various evidence showing the pro-inflammatory role of MBL in tissue damage and severity of other inflammatory diseases, particularly in cardiovascular disease [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the oxidative stress generated by the severe inflammation contributes to valve damage [5]. A study by Chen et al (2012) showed that the increased inflammation was significantly correlated to the increase of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there were no correlations between the TOS and OSI values in the study cohort. Hence, it was declared that oxidative stress had no pronounced effect on the etiopathogenesis of congenital heart valve disorders during childhood (19).…”
Section: Discussionmentioning
confidence: 99%